2014
DOI: 10.3354/meps10604
|View full text |Cite
|
Sign up to set email alerts
|

Trophodynamics of anchovy in a non-upwelling system: direct comparison with sardine

Abstract: Anchovies and sardines hold a very important position in pelagic ecosystems and are usually found in species pairs, exhibiting fluctuations in abundance. In upwelling systems, alternations in small pelagic fish have been hypothesized to be, at least partly, trophically mediated. In non-upwelling areas, direct comparisons of sardine and anchovy trophodynamics are lacking, which represents an impediment to our understanding of forage fish interactions. In the present study, we analyzed the diel feeding periodici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 45 publications
2
39
1
2
Order By: Relevance
“…The duration of metamorphosis is known to be related to temperature: in laboratory experiments for the summer flounder (Paralichthys dentatus) and the Pacific tarpon (Megalops cyprinoides), Keefe and Able (1993) and Chen et al (2008), respectively, showed that the course of metamorphosis was clearly temperature dependent. Also, in a recent study, Nikolioudakis et al (2014) demonstrated that morphological changes associated with metamorphosis are more abrupt in species developing in summer (high temperature) but more gradual in those developing in winter (low temperature).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The duration of metamorphosis is known to be related to temperature: in laboratory experiments for the summer flounder (Paralichthys dentatus) and the Pacific tarpon (Megalops cyprinoides), Keefe and Able (1993) and Chen et al (2008), respectively, showed that the course of metamorphosis was clearly temperature dependent. Also, in a recent study, Nikolioudakis et al (2014) demonstrated that morphological changes associated with metamorphosis are more abrupt in species developing in summer (high temperature) but more gradual in those developing in winter (low temperature).…”
Section: Discussionmentioning
confidence: 95%
“…Also, in a recent study, Nikolioudakis et al . () demonstrated that morphological changes associated with metamorphosis are more abrupt in species developing in summer (high temperature) but more gradual in those developing in winter (low temperature).…”
Section: Discussionmentioning
confidence: 97%
“…Anchovy juveniles feed exclusively on mesozooplankton (Nikolioudakis et al 2014b), and postflexion anchovy larvae derive the bulk of their energy from mesozooplankton (Borme et al 2009). Coupled hydro-biogeochemical models, many of which are currently being developed and validated in several ecosystems around the world, comprise a unique means of simulating prey fields available for planktivorous fish on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…These taxa exert a significant grazing impact on phytoplankton and microzooplankton (Siokou-Frangou et al, 2002;Gaudy et al, 2003;Zervoudaki et al, 2007), modulate the response of the microbial food web to nutrient availability (Pasternak et al, 2005), and are the major prey of small pelagic fish (Tudela & Palomera, 1997;Nikolioudakis et al, 2014). Coastal Mediterranean mesozooplankton communities are typically more abundant than in the open Sea, but less diverse in terms of species composition and can differ in terms of species dominance (Gaudy, 1985;Fernández de Puelles et al, 2003).…”
Section: Introductionmentioning
confidence: 99%